Industrial clusters: A scientific review mapping - Jiménez Hernández, Iván Saúl; Trejo Guardado, Rubén; Solís Gálvez, Claudia Elena (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. This research aimed to carry out a scientific mapping to identify the knowledge currently emerging regarding the agglomerations of companies and institutions called Industrial Clusters through a literature review of theoretical foundations and existing empirical research. Design/Methodology/Approach. Bibliometric techniques have been used for this research work, in addition to other techniques, such as scientific mapping approaches and performance analysis based on the h-index and joint word analysis. The SciMAT software was used to analyze scientific maps due to its visualization and duplication process, which are based on thematic areas and strategic diagrams. The bibliometric methodology comprises four phases: 1. Location of research topics; 2. Visualization of thematic network and research topics; Findings of thematic areas; and 4. Performance analysis. Results/Discussion. From 2005 to 2011, the strategic diagram and the performance indicators identified eighteen related research topics. Sixteen research topics were identified from 2012 to 2016. Finally, from 2017 to 2020, fourteen research topics were identified. Conclusions. We consider that the central theme of this study (Industrial Clusters) represents a niche for research and the generation of knowledge in areas of expertise such as Engineering, Environmental Science, Business, Management and Accounting, Computer Science, Earth and Planetary Sciences, and Social Sciences, among others. Likewise, the research topics within these thematic areas considered necessary for their contribution to the growth of the field are Mining-Industry, International-Organization, Wind-Power, Emission-Control, Manufacturing-Sector, Government-Relations, Regional-Authorities, and Economical -And-Social-Effects. Originality/Value: This work analyzes the current bibliographic production of Industrial Clusters, which opens a range for new research.